Pakistan Distance-Learning Topic Brief: Primary-level Deaf Children - Lynch, Paul; Kaye, Tom; Terlektsi, Emmanouela (EdTech Hub, 2020)
The COVID-19 crisis has severely impacted the ability of national education actors to provide access to education services for all students.This brief provides guidance and recommendations on how to support the education of deaf children in Pakistan using alternative learning approaches. It presents the rationale for adopting certain teaching and learning strategies when supporting the learning and well-being of deaf children during global uncertainty. Children with deafness and hearing loss are particularly vulnerable now that schools are closed. They are isolated at home and unable to access information as easily as when they were attending school. This brief presents some of the practices that are reportedly working well for deaf children in different contexts.
EdTechHub.Source: 2405685:LP4PGMNA KerkoCite.ItemAlsoKnownAs: 10.5281/zenodo.3891379 2129771:3YH4WC8N 2129771:7J2S7YUK 2129771:J35ZR45N 2339240:CUSR6ZBJ 2339240:FS3CFIBL 2339240:N7RDGZGY 2339240:V229A7WT 2405685:4PAZ4ZQH 2405685:LP4PGMNA 2405685:XIQ5CL9B 2405685:YY4LI6EI
Keywords: C:Pakistan; F: Helpdesk response; L:Special education needs and disabilities (SEND); LP: English; _C:Bangladesh BGD; _C:Ethiopia ETH; _C:India IND; _C:Ireland IRL; _C:Kenya KEN; _C:Pakistan PAK; _C:Rwanda RWA; _C:United Kingdom GBR; _C:United States USA; _DOILIVE; _EdTechHub_Output; _GS:indexed; __C:filed:1; __C:scheme:1; _cover:v1; _r:CopiedFromEvLib; _r:ImportedToMyEducationEvidence; _zenodoETH; docs.opendeved.net; dode_eth-src-eth; dode_eth-trf2-dode